Design thinking program on the google classroom platform on creativity in high school students - Tenorio-Molina, Gladys; Medina-Altamirano, Naara; Enriquez-Gavilan, Nerio; Quispe-Solano, Monica; Lopez-Curasma, Aydeé; Cochachi-Quispe, Angel (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: The problem in this topic lies in the lack of focus on the development of creative and problem-solving skills in high school students at Institution No. 6152 in Lima during the year 2022. This deficiency can limit their ability to tackle the challenges of the present and future world, making it necessary to implement a Design Thinking program on the Google Classroom platform to address this issue.OBJECTIVES: The objective of this research was to evaluate the effects of the design thinking program in the google classroom platform on creativity in high school students of Institution N°6152, Lima-2022.METHODS: The methodology was conducted under a quantitative approach, applied, with a quasi-experimental design, with 30 students in the experimental group and 24 in the control group.RESULTS: The creativity instrument was applied before and after the program to both groups. In the descriptive results of the general objective, in the experimental group of the pre-test, 80% were at a moderate level and 20% at a low level, and after the program was applied, 50% were at a moderate and high level , so there were changes in creativity. It is concluded with the result of the student’s t-test finding ap value = 0.029 < 0.05 that the google classroom program significantly improved creativity in high school students of the institution N°.6152,Lima.2022.CONCLUSION: the Design Thinking program on the Google Classroom platform aimed at fostering creativity in high school students at Institution No. 6152 in Lima during 2022 addresses the lack of creative and problem-solving skills. This educational approach prepares students to tackle contemporary challenges by promoting empathy, collaboration, and experimentation. It represents a valuable investment in their future, equipping them to excel in an ever-changing world.
Keywords: Creativity; imagination; design; invention; thought; students